Efeito da Intervenção Cultural na Caracterização Morfológica de Diferentes Proveniências de Quercus suber (Silva Lusitana, 2013)
The cork oak (Quercus suber L.) is a very important species in Mediterranean areas for economic, ecological and environmental reasons. It is a species with high potential of expansion considering the scenarios of climate change. Despite its importance, cork oak adaptability to environmental conditions is poorly understood. In order to understand the genetic determinism of adaptive traits and study patterns of adaptive variation at landscape level, assuming there is genetic differentiation in phenological traits found at the population level, we established a trial in Mogadouro – Trás-os-Montes, with 34 provenances of Q. suber from its natural Mediterranean distribution area. Considering that not only the adaptation of the species, but also the improvement of the reproductive material both in tree form and quality of cork are important, and that the improvement of the tree form can be artificially induced by training technique, in this work we tested the influence of training cuts to improve tree form of the provenances. Morphological characterization of the provenances was performed using the evaluation of qualitative characteristics of the stem as inclination and dominance of the stem using a scale of 1 (worst feature) 6 values (best feature), before the cuts and five years after its application. Tree training seems to have no effect or have very little effect on the ranking of the provenances that have previously revealed the worst morphological characteristics as the group of the Italian and French and some provenances of the groups of Portuguese and Spanish. The Moroccan provenances show good adaptive features that are enhanced by training cuts.